Les Algues Indicatrices De L'eutrophisation Et De La Contamination De La Lagune De Korba (Cap Bon Tunisie) - R ., Rahmouni; S., Bouden; W., Oueslati; A., Sbei; F., Chaabani (European Scientific Journal, ESJ, 2016)
The concentrations of heavy metals (Fe, Zn, Pb and Mn) were determined in two green algae (Enteromorpha intestinalis and Chaetomorpha Linium) collected from April 2012 to February 2013 in nine stations characterized by the abundance of these algae throughout the year. Determination of Pb, Mn and Zn was carried out by graphite furnace atomic absorption spectrometer while Fe by flame atomic absorption spectrometer (using the Thermo Scientific ICE 3300 AA Spectrometer). An evaluation of the degree of eutrophication is made through the physicochemical study of 31 samples in the surface water. The results underline that Korba is an eutrophic lagoon. The heavy metal concentrations in the water samples decreased in the sequence of Fe >Zn > Mn > Pb, while in Chaetomorpha Linium, Enteromorpha intestinalis and sediment exhibited the same pattern across the sites: Fe >Mn> Zn >Pb. The results show that metal accumulation capacity in both macro-algae varies according to the season and depends on the species. By comparison with other studies in the world, the levels found in the algae of Korba lagoon are relatively high except Mn. Chaetomorpha Linium could be used as an excellent indicator for heavy metals accumulation in Korba lagoon.